SQL server database programming with C# : desktop and web applications - Bai, Ying (Boca Raton, FL : CRC Press, 2024)
"Databases have become an integral part of modern-day life. We live in an information-driven society. Database technology has a direct impact on our daily lives. Decisions are routinely made by organizations based on the information collected and stored in the databases. Because databases play such an important role in business and society, database programming is a key skill. SQL Server Database Programming with C#: Desktop and Web Applications is for college students and software programmers who want to develop practical and commercial skills in database programming with C# or Visual C#.NET 2022 as well as the relational database Microsoft SQL Server 2019. The book explains the practical considerations and applications in database programming with Visual C# 2022 and provide realistic examples and detailed explanations. A direct writing style is combined with real-world examples to provide readers with a clear picture on how to handle database programming issues in the Visual C#.NET 2022 environment. Highlights include: A complete sample database CSE_DEPT built with Microsoft SQL Server 2019 Express is provided and used for the entire book. Step by step, detailed illustrations and descriptions show how to design and build a practical relational database. Both fundamental and advanced database-programming techniques are covered to benefit beginning students and experienced programmers. An advanced database query technique, LINQ API that includes LINQ to Objects, LINQ to DataSet, LINQ to SQL, LINQ to Entities and LINQ to XML, is discussed, analyzed, and implemented in actual projects with line-by-line explanations. Homework and class projects are provided for each chapter to strengthen and improve students' abilities of learning and understanding for topics they studied. PowerPoint teaching slides and selected homework solutions help instructors to teach and organize their classes easily and effectively. Useful and practical, this textbook is an intuitive guide on how to develop and build professional and practical database applications"--Provided by publisher.
Includes index.
Keywords: SQL server; Database management; Web applications